2012
DOI: 10.1039/c2jm31792c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of aminosilane–alginate hybrid microcapsules and their use for enzyme encapsulation

Abstract: Organic-inorganic hybrid microcapsules (AP-capsules) were fabricated by sequential preparation of calcium alginate microcapsules (Alg-capsules), followed by the addition of the Alg-capsules to an aqueous solution of 3-aminopropyltriethoxysilane (APTES) in mild conditions without the use of any catalyst. Results showed that the shell thickness of AP-capsules was found to vary with time during the APTES incorporation onto the Alg-capsules, suggesting that the shell thickness was dependent on the amount of CaCl 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…EDX analysis confirmed the existence of Si (AAPTS) and calcium in the shell of AEA‐capsule (Figure F). Our previous studies, describing two‐step preparation method of alginate‐aminosilane hybrid capsules, have shown that soaking of Alg‐capsules in an aqueous solution containing aminopropyltriethoxysilane (APTES) induced gradual shrinkage of alginate shell along the thickness direction with time course and finally formed thin shell membrane with homogenous structure . The results of the morphological and EDX analyses were consistent with those obtained in the previous study.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…EDX analysis confirmed the existence of Si (AAPTS) and calcium in the shell of AEA‐capsule (Figure F). Our previous studies, describing two‐step preparation method of alginate‐aminosilane hybrid capsules, have shown that soaking of Alg‐capsules in an aqueous solution containing aminopropyltriethoxysilane (APTES) induced gradual shrinkage of alginate shell along the thickness direction with time course and finally formed thin shell membrane with homogenous structure . The results of the morphological and EDX analyses were consistent with those obtained in the previous study.…”
Section: Resultssupporting
confidence: 87%
“…Our previous studies, describing two-step preparation method of alginate-aminosilane hybrid capsules, have shown that soaking of Alg-capsules in an aqueous solution containing aminopropyltriethoxysilane (APTES) induced gradual shrinkage of alginate shell along the thickness direction with time course and finally formed thin shell membrane with homogenous structure. 23,24 The results of the morphological and EDX analyses were consistent with those obtained in the previous study. Therefore, these results suggested that AAPTS was successfully incorporated into alginate shell via an electrostatic interaction between positively charged amino groups of AAPTS and negatively charged carboxyl groups of alginate along with polycondensation of AAPTS.…”
Section: Observation Of Aea-capsulessupporting
confidence: 89%
“…The values of enzyme activity retained in the seed coating layer may be related to the coating process. Firstly, leakage of the enzyme can occur during the encapsulation process, probably before the alginate capsule was formed, which could result in a decrease in the calculated coating yield. Thus Vikartovská et al reported enzyme losses of about 56% during the first step of the encapsulation of glucose oxidase in polyelectrolyte complex capsules.…”
Section: Discussionmentioning
confidence: 99%
“…a. The use of alginate–enzyme immobilization has a good track record for biotechnological applications, which are listed in Table . Several studies have shown that immobilized enzymes are functionally active and can be reused up to several cycles.…”
Section: Discussionmentioning
confidence: 99%